INTEGRATION OF BIODEGRADATION AND MIGRATION OF HYDROCARBONS IN A 2D PETROLEUM SYSTEMS MODEL: APPLICATION TO THE POTIGUAR BASIN, NE BRAZIL. (January 2016) - Ducros, M.; Carpentier, B.; Wolf, S.; Cacas, M‐C.
Abstract : Biodegradation is probably the most important in‐reservoir alteration process and is responsible for the majority of the known heavy oil accumulations. In the present study, biodegradation processes were integrated within a forward basin and petroleum systems model applied to the Potiguar Basin, NE Brazil. This basin was chosen because it has been studied in detail and data from previous investigations are publically available. In order to account for processes occurring during the biodegradation of hydrocarbons, the evolution of fluid properties was simulated through time. In the model, a new approach was developed in order to determine the intensity of microbial activity and the evolution of the oil‐water contact, the zone within which biodegradation is confined. The numerical results obtained by applying the forward simulator to a 2D model of the Potiguar Basin fit the observed data concerning the composition and quality of the oil in a series of oilfields. These accumulations are located along the NE‐SW oriented "Carnaubais trend" and show progressive biodegradation along the migration path from the offshore kitchen area. Our results show that the biodegradation trend observed along the cross‐section can in general be explained by the fact that reservoirs are successively filled as a result of spilling from previous reservoirs, with continuous hydrocarbon degradation occurring within the reservoirs. This charge history resulted in differences in the composition of oils transported from upstream to downstream reservoirs, and in the evolution over time of the ratio between biodegradation and reservoir filling rates. Thus, in addition to residence time in the biodegradation temperature window, the rate of reservoir infill, the rate of oil degradation and the migration pathways are key factors controlling biodegradation. This study also demonstrates how the approach developed within our petroleum system simulator, which integrates both migration and biodegradation, may improve the assessment of oil quantity, quality and migration timing.